Creativity and performance. Testing ambidextrous hypotheses in the context of Polish SME’s - Bratnicka-Myśliwiec, Katarzyna (Twórczość i efektywność. Testując hipotezy obustronności w kontekście polskich małych i średnich przedsiębiorstw, 2016)
This study; using data from 158 small and medium-sized Polish enterprises; develops the theory on how organizational creativity links to a firm’s performance. I address this gap by studying the varying impact of creative novelty and creative usefulness on a firm’s profitability and growth. Drawing on the firm’s performance theory; I find that objective and subjective measures have distinct performance effects. As a result; organizational creativity becomes effective in different ways. Broadly speaking; these findings have important implications for organizational creativity research
Management Forum, 2016, vol. 4, no. 3, s. 9-15
Keywords: organizational creativity; firm’s performance; organizational ambidexterity; twórczość organizacyjna; efektywność organizacyjna; obustronność organizacyjna